2003
DOI: 10.1038/sj.onc.1206042
|View full text |Cite
|
Sign up to set email alerts
|

The human LASP1 gene is fused to MLL in an acute myeloid leukemia with t(11;17)(q23;q21)

Abstract: The MLL gene at chromosome 11q23 is frequently rearranged in acute leukemia. Here we report the identification of a new MLL fusion partner in the case of an infant with AML-M4 and a t(11;17)(q23;q21) translocation. Fluorescence in situ hybridization (FISH) and RT-PCR analyses indicated a rearrangement of the MLL gene, but no fusion with previously identified MLL fusion partners at 17q, such as AF17 or MSF. Rapid amplification of cDNA ends (RACE) revealed an in-frame fusion of MLL to LASP1, a gene that is ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 27 publications
0
31
1
2
Order By: Relevance
“…Two additional observations underscore the importance of LASP-1 in cancer. First, altered expression of LASP-1 is associated with the MLL gene in acute myeloid leukaemia (Strehl et al, 2003). Second, recent studies have shown LASP-1 to be transcriptionally upregulated in response to the morphogen Sonic Hedgehog (Ingram et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Two additional observations underscore the importance of LASP-1 in cancer. First, altered expression of LASP-1 is associated with the MLL gene in acute myeloid leukaemia (Strehl et al, 2003). Second, recent studies have shown LASP-1 to be transcriptionally upregulated in response to the morphogen Sonic Hedgehog (Ingram et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Apparent translocations fused MLL to sequence located on chromosome bands 3q26, 3p25, 4q31-32, 4p15, 6q21, 7q31-32, 9q21-22, 12q21 (2 clones), 14q21, 15q12-13, 17q24 (3 clones), and Xq22-23. Although several of these chromosomal bands contain known partner genes of MLL (3q25-26-GMPS, 6q21-AF6q21, 17q24-LASP1, and Xq22-23-Septin6 [56][57][58][59] ), the partner sequences in the induced clones did not match known MLL partners.…”
Section: Ipcr Analysis Of Etoposide-induced Mll Repair Productsmentioning
confidence: 99%
“…이중 4개의 MLL 결합파트너 유 전자가 17번 염색체 장완에 존재하는 것으로 보고되었는데 ALL1 fused gene from chromosome 17 (AF17 혹은 MLLT6, 17q21 에 위치), LIM and SH3 protein (LASP1 혹은 MLN50, 17q21 에 위치), MLL septin-like fusion (MSF 혹은 SEPT9, 17q25 에 위치) 및 RARA (17q21에 위치) 유전자이다 [10][11][12][13].…”
Section: 김경은•김성현•한진영unclassified
“…현재까지 APL의 변이형에서 보이는 t(11;17)(q23;q21)의 염 색체 변이를 나타내면서 형태학적으로는 APL이 아닌 AMoL으 로 진단된 증례가 전 세계적으로 7-8예 정도 보고되고 있다 [7,[10][11][12][13][14][15][16][17]. …”
Section: 김경은•김성현•한진영unclassified